Revisiting Stock Market Integration Pre-Post Subprime Mortgage Crisis: Insight From BRIC Countries - Brahmana, Rayenda; Puah, Chin-Hong; Wong, Kai-Hung (Economics and Finance in Indonesia, 2015)
This study revisits the long-run relationships and short-run dynamic causal linkages among BRIC stock market, with the particular attention to the 2008 subprime mortgage crisis. Extending related empirical studies, comparative analyses of pre-crisis, and post-crisis periods were conducted to comprehensively evaluate how stock market integration was affected by financial crises. In general, after employing cointegration test and VAR test, the results reveal the increase of stock market integration in BRICs after the subprime crisis. The evidence also found that China stock market is the most influential among the BRICs, in which China stock market has the ability to Granger cause the other three BRICs member countries. An important implication of our findings is that the degree of integration among countries tends to change over time, especially around periods marked by financial crises.